Influence of winds on temporally varying short and long period gravity waves in the near shore regions of the eastern Arabian Sea - Glejin, J.; SanilKumar, V.; Nair, T.M.B.; Singh, J. (European Geosciences Union, 2013)
Wave data collected off Ratnagiri, west coast of India, during 1 May 2010 to 30 April 2012 are used in this study. Seasonal and annual variations in wave data controlled by the local wind system such as sea breeze and land breeze, and remote wind generated long period waves are also studied. The role of sea breeze on the sea state during pre- and postmonsoon seasons is studied and it is found that the maximum wave height is observed at 15:00 UTC during the premonsoon season, with an estimated difference in time lag of 1-2 h in maximum wave height between premonsoon and postmonsoon seasons. Observed waves are classified in to (i) short waves (T sub(p) less than 8 s), (ii) intermediate waves (8 less than T sub(p) less than 13 s), and (iii) long waves (T sub(p) more than 13 s) based on peak period (T sub(p)) and the percentages of occurrence of each category are estimated. Long period waves are observed mainly during the pre- and the postmonsoon seasons. During the southwest monsoon period, the waves with period more than 13 s are a minimum. An event during 2011 is identified as swells propagated from the Southern Ocean with an estimated travelling time of 5-6 days. The swells reaching the Arabian Sea from the south Indian Ocean and Southern Ocean, due to storms during the pre- and postmonsoon periods, modify the near surface winds due to higher phase wave celerity than the wind speed. Estimation of inverse wave age using large-scale winds such as NCEP (National Centers for Environmental Prediction) reflects the presence of cyclonic activity during pre- and postmonsoon seasons but not the effect of the local sea breeze/land breeze wind system.